Relationship between Ethical Work Climate and Ethics Factors, and Their Influence on Moral Judgement Competence of Academicians in Private Institutions of Higher Learning - Sin, Chek Neng (2006)
The move towards corporatisation of Malaysian public universities and the establishment of a number of private institutions of higher learning were made to establish Malaysia as one of the regional educational hubs and a centre for providing educational excellence. However, the rapid expansion of private education institutions owned by profit-driven enterprises have posed a number of ethical problems and issues, such as the lack of a code of practice and the drive towards profit maximisation at the expense of a quality education. Issues such as corporate integrity and accountability are being questioned, and professionals are now finding ways to promote and inculcate ethical culture to these organisations. A number of studies have shown that there is clearly a relationship between the corporate organisations and individuals who work in the organisation when it comes to morals or ethics. Corporations could only act as a result of the choices and actions of human individuals in the corporations. This clearly shows that ethical culture of corporations, like the private institutions of higher learning can be affected by the ethical behaviour of the individuals, especially the academic staff. This study was conducted to determine the level of moral judgement competence of academic staff in the private institutions of higher learning, and its relationship with ethical work climate and ethics factors. The research design of this study was a correlational research using a cross-sectional survey approach. Four hundred and six (406) academic staff in Malaysia participated in this study by returning the self-administered questionnaire distributed to them. For computation and analysis of data collected, the Statistical Package for the Social Sciences (SPSS) for Windows program was used. The findings revealed more than 78.1% of the academic staff had a medium level of moral judgement competence. The findings also indicated the emergence of the instrumental and service dimensions as two dominant dimensions of ethical work climates in the private institutions of higher learning. The relationship between moral judgement competence, ethical work climate, demographic factors, professional factors, and ethic factors were tested and the conclusions of the findings were mixed. However, seven hypotheses tested in this research confirmed that the ethical work climate dimensions and the selected ethics factors had positive and significant relationship with moral judgement competence. The result suggests that consideration must be made with regards to demographic, professional and ethics factors when deciding on any human resource policies and development. The move towards institutionalising ethics through formulation of codes of ethics, formalising ethics training, factoring ethics in performance management and nurturing right ethical climate in the workplace can significantly accelerate the rate of moral development and moral judgement competence.